2017
DOI: 10.1177/0969733017700237
|View full text |Cite
|
Sign up to set email alerts
|

Ethics interventions for healthcare professionals and students: A systematic review

Abstract: Patient-related outcomes followed by organisational outcomes can be improved by ethics interventions targeting professionals. Such outcomes are promising in developing ethical safety for healthcare patients and professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 66 publications
1
26
0
Order By: Relevance
“…Furthermore, further ethics education is positively connected to physiotherapist's self-estimated ethical competence. That result is consistent with previous research which notes that ethical competence can be acquired through education [4,21,24]. Taking part in ethics education after graduation is still very uncommon among physiotherapists (20% had participated).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, further ethics education is positively connected to physiotherapist's self-estimated ethical competence. That result is consistent with previous research which notes that ethical competence can be acquired through education [4,21,24]. Taking part in ethics education after graduation is still very uncommon among physiotherapists (20% had participated).…”
Section: Discussionsupporting
confidence: 92%
“…All interaction with patients should be humanoriented, recognizing more clearly an individual patient in the center, to ensure dignity and respect in care [2]. This requires ethical competence of a professional and can be acquired through educational interventions [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…To gain a deeper understanding of ethical competence, different multidimensional designs are needed. Intervention studies using educational interventions may offer a possibility to have an impact on the ethical competence of healthcare professionals (Stolt, Leino‐Kilpi, Ruokonen, Repo, & Suhonen, ). Most commonly, studies reported low‐response rates and sampling/participant bias as their limitations.…”
Section: Discussionmentioning
confidence: 99%
“…The management and governance of healthcare organizations do face ethical challenges in the wake of competing needs or values or even in meeting various shareholders' demands etc. This is a likely happening in a competitive market, and also in markets, where consumers have limited knowledge, face uncertainty, and have to depend on marketers to provide ethical, customer-oriented guidance (Bush, Harris, & Bush, 1997;Stolt, Leino-Kilpi, Ruokonen, Repo, & Suhonen, 2018).…”
Section: Background Of the Studymentioning
confidence: 99%
“…It can easily be seen that this is not an absolute case of one-sided (from employees' end only) ethical challenge. Research in healthcare sector has highlighted that in facing an ethical dilemma when healthcare professionals perceive that their ethical standards are not shared or met by their respective organizations, these professionals go through an increased rate of burnout (Stolt et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%